(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Background: The nursing profession faces numerous challenges, including staffing shortages, burnout among healthcare workers, and the need for effective leadership in healthcare settings. This abstract provides a synthesis of selected studies investigating various aspects of nursing practice and healthcare management to address these challenges. Aim: The aim of this abstract is to summarize the key findings and implications of the selected studies, which explore topics such as nurse job dissatisfaction, leadership effectiveness, and strategies for managing healthcare staff during crises. Method: A comprehensive review of relevant literature was conducted to identify studies addressing the aforementioned topics. A total of twelve studies were selected based on their relevance to the research questions and their contributions to the understanding of nursing practice and healthcare management. Results: The selected studies provide insights into the factors contributing to nurse job dissatisfaction, including workload, work-life balance, and leadership effectiveness. Additionally, the studies highlight the importance of effective leadership in healthcare settings, particularly during crises such as the COVID-19 pandemic. Strategies for managing healthcare staff during crises, such as proactive staffing measures and support mechanisms for frontline workers, are also discussed. Conclusion: The findings of the selected studies underscore the need for healthcare organizations to prioritize efforts to address nurse job dissatisfaction, enhance leadership capabilities, and promote the well-being of frontline healthcare workers. By implementing evidence-based strategies to support nursing professionals and healthcare managers, organizations can optimize patient care outcomes and create supportive work environments conducive to staff well-being and retention.